Critical Response: “Teaching Approaches: Theory and Practice” by Olessya Akimenko - Ivatov, Serik (NUGSE Research in Education, 2(2), 2017)
In her article published by NUGSE Research in Education in December 2016, Akimenko discusses the theoretical understandings of teacher-centred and student-centred approaches, and examines these theories with regard to teaching approaches in Kazakhstan. Teaching approaches have been studied very well abroad so that they can be considered as old chestnuts. However, Kazakhstan will likely benefit greatly from a comparison of teaching approaches in international and Kazakhstani practices. If we study international practices, we will get better understanding of our own. In addition, comparative research may help us to discover which teaching approaches are beneficial and how best to implement them. I agree with the author’s position that Kazakhstani teachers should take advantage of teaching approaches from international practice; however, she does not manage to accomplish all her goals set in the article.
Keywords: teaching approaches; Olessya Akimenko